Grazing-Induced Habitat Degradation: Challenges to Giant Panda Survival Resulting from Declining Bamboo and Soil Quality - Huawei Tian; Ying Zeng; Zejun Zhang; Ming Lu; Wei Wei (Animals)
Grazing is the primary human-induced disturbance affecting giant panda (Ailuropoda melanoleuca) habitats and has a severe impact on the long-term sustainability of the giant panda population. To address the lack of quantitative studies on grazing’s impact on habitat quality, we selected China’s most heavily grazed giant panda nature reserve. Utilizing the Maxent model and stoichiometric analysis, we investigated habitat quality degradation caused by grazing and quantified changes in bamboo nutritional quality and soil physicochemical properties. The results indicate that grazing has significantly reduced the suitable habitat area for giant pandas from 101.87 km2 to 80.64 km2. Specifically, high-suitability habitats declined by 14.14%, moderate-suitability habitats declined by 22.70%, and low-suitability habitats declined by 22.88%. Grazing has forced pandas to move to higher altitudes (2650–3057 m) with taller (12–20 m) trees, denser (28–55 plants) shrubs, and sparser (30–69%) bamboo. Additionally, the soil water content has decreased, while soil bulk density, total N, available N, and pH have significantly increased. Reductions in crude protein and ether extract, along with increased crude fiber and ash, have lowered bamboo’s nutritional value and palatability. This study elucidates how grazing degrades giant panda habitat quality and provides a scientific basis for its conservation management.